STLR4/MD-2 complex inhibits colorectal cancer migration and invasiveness in vitro and in vivo by lncRNA H19 down-regulation. (28th September 2017) - Liang, Weijun; Zou, Yan; Qin, Fengxian; Chen, Jifei; Xu, Junyi; Huang, Shifeng; Chen, Jingfan; Dai, Shengming
Abstract: Long non-coding RNAs (lncRNAs) have multiple functions in gene regulation and during cellular processes. However, the functional roles of lncRNAs in colorectal cancer (CRC) have not yet been well understood. In our previous study, we demonstrated that sTLR4/MD-2 complex can inhibit CRC in vitro and in vivo by targeting LPS. Therefore, the aim of the present study is to investigate the expression of lncRNA H19 in CRC and to evaluate its effect on the inhibition of sTLR4/MD-2 complex. The expression of H19 is measured in 63 CRC tumor tissues and adjacent normal tissues by quantitative real-time PCR (qRT-PCR). The effects of H19 on migration and invasiveness are evaluated by wound healing assay, migration and invasion assays. Results showed that H19 is significantly overexpressed in cancerous tissues and CRC cell lines compared with adjacent normal tissues and a normal human intestinal epithelial cell line. Moreover, H19 overexpression is closely associated with CRC patients. Our in vitro data indicated that knockdown of H19 inhibits the migration and invasiveness of CRC cells. And in vivo sTLR4/MD-2 complex inhibits tumor growth in mice and the expression of H19 is down-regulated. These results suggest that sTLR4/MD-2 complex inhibits CRC migration and invasiveness in vitro and in vivo by lncRNA H19 down-regulation.